An observational study of seatbelt use among vehicle occupants in Nigeria (2009)
Objective: The use of seatbelts reduces the likelihood of death and severe injuries to crash-involved vehicle occupants by 45e60%. Several countries, including Nigeria, have laws mandating the use of seatbelts but compliance is not universal. This study was conducted to determine rates of use of seatbelts among vehicle occupants in Ibadan municipality. Design: An observational study was conducted. A selected petrol station in each of the five local government areas in Ibadan municipality was used as an observation site. Observations were documented by trained research staff between 08:30 and 18:00 hours over a 6-day period. Results: 5757 occupants in 2870 vehicles were observed. Approximately 90% of drivers were men. Driver seatbelts were installed in approximately 90% of vehicles. Overall seatbelt use was 18.7; 31.7% among drivers and 10.3% and 0.4% among front and rear-seated adults, respectively. Only one child (0.7%) was restrained. Significantly more female drivers 47.3% used their seatbelts compared with men, 30.3% (p<0.001). An adult passenger was more likely to be restrained when riding with a female driver (p=0.007) and when the driver was restrained (p=0.000). Conclusions: The study showed that seatbelt use among vehicle occupants was low. Further research into reasons for the non-use of restraints needs to be conducted so that these can be incorporated into programmes aimed at improving seatbelt use.